Initial Design and Development of Business Process Architecture at Universitas Negeri Manado Library - Dalle, Arisa (The Indonesian Journal of Computer Science, 2025)
Analyzing, reengineering, improvement, and business process architecture in defining and managing various business processes in an organization. The problem that occurs is the comparison of the business processes carried out and the comparison of business procedures that have been set in the SOP (standard operating procedures). So that it affects the efficiency in carrying out an activity or activity. In calculating the similarity between the two business processes by calculating the similarity of business process models using the jaccard method. The purpose of this research is BPMN modeling that allows continuous improvement, better service development, and adjustment to changes in the library environment. From the results of the equation calculation using jaccard, the average is 0.862222222 with a standard deviation of 0.172639638. So that shows the more similar between the two business process models because the average value is close to one.